2022
DOI: 10.1109/jiot.2021.3126614
|View full text |Cite
|
Sign up to set email alerts
|

Lab-on-a-Fish: Wireless, Miniaturized, Fully Integrated, Implantable Biotelemetric Tag for Real-Time In Vivo Monitoring of Aquatic Animals

Abstract: In vivo electronic monitoring systems for underwater applications are promising technologies for obtaining information about aquatic animals. State-of-the-art devices are constrained by limits on the number of integrated sensors, large dimensions and weight, and short device longevity. Here, we report the Labon-a-Fish: the world's first biotelemetry tag that combines edge computing with wireless sensing of in vivo physiology [electrocardiogram (ECG) and electromyogram (EMG)], behavior [activity level and tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Bioelectric tag is one of the most widely used devices for fish behavioral studies. Fish tags are required to be as small and light as possible to minimize the burden of the device on the fish. However, existing fish tags usually require cumbersome batteries, which limits the lifetime and miniaturization of the device. Energy harvesting systems based on vibrational motion and mechanical deformation are promising candidates for self-powered fish tags. Piezoelectric nanogenerators have attracted great attention because they can potentially scavenge inexhaustible biomechanical energy with a high output voltage. Dagdeviren et al proposed a flexible PZT nanogenerator that enables high-efficiency mechanical-to-electrical energy conversion from the natural contractile and relaxation motions of the heart, lung, and diaphragm . Lu et al reported an implantable ultra-flexible piezoelectric nanogenerator that harvests the mechanical energy from the heart movements of pigs .…”
Section: Introductionmentioning
confidence: 99%
“…Bioelectric tag is one of the most widely used devices for fish behavioral studies. Fish tags are required to be as small and light as possible to minimize the burden of the device on the fish. However, existing fish tags usually require cumbersome batteries, which limits the lifetime and miniaturization of the device. Energy harvesting systems based on vibrational motion and mechanical deformation are promising candidates for self-powered fish tags. Piezoelectric nanogenerators have attracted great attention because they can potentially scavenge inexhaustible biomechanical energy with a high output voltage. Dagdeviren et al proposed a flexible PZT nanogenerator that enables high-efficiency mechanical-to-electrical energy conversion from the natural contractile and relaxation motions of the heart, lung, and diaphragm . Lu et al reported an implantable ultra-flexible piezoelectric nanogenerator that harvests the mechanical energy from the heart movements of pigs .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with machine vision, biosensor technology has the advantage of not being affected by light. Biosensor technology has been widely used in recognizing swimming, feeding, friction, escape and reproduction behaviour in fish, 12–14 which is of great significance to observe the behaviour of fish and adjust breeding strategies. Unfortunately, biosensor technology commonly requires a tag to be implanted inside the fish, which means the process is invasive 15 .…”
Section: Introductionmentioning
confidence: 99%
“…NDERWATER acoustic telemetry finds diverse applications in fields of subsea resource extraction such as resource exploration [1] , tracking the movements of aquatic and marine animals [2,3] , wireless communications for autonomous underwater vehicles (AUVs) [4] , and the emerging Internet of Underwater Things (IoUT) [5][6][7][8] . However, unlike terrestrial wireless communications systems, state-of-the-art acoustic telemetry systems suffer from limited data rates and energy efficiency, because of the characteristics of underwater communication, including bandwidth-limited underwater acoustic channels -generally recognized as the most challenging communication media in use today [9] -caused by high path loss [8] , time-varying multipath propagation [10] , large and variable propagation delay, node mobility caused by water currents [1] , and Doppler spread associated with the complex underwater environment [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Research and practice on this emerging technology have led to a wide spectrum of applications, including live video analytics, agriculture, and smart home and industrial Internet of Things (IoT) devices [24] . Recently, the authors have developed the Lab-on-a-Fish: a miniaturized biotelemetry tag that combines edge computing for studying the aquatic animals with improved efficacy [3] . Edge computing offers a new strategy for shorter latency and effective bandwidth usage for underwater acoustic communication [25] .…”
Section: Introductionmentioning
confidence: 99%